El continuo de la psicosis: Evidencia psicométrica (2023)
This paper has two goals. The first is to determine the factor structure of the proneness to hallucination in a sample of the Colombian population using the Launay-Slade Hallucination Scale Revised (LSHS-R). The second goal is to compare the results of the non-clinical population with the results of a group of patients diagnosed with schizophrenia. The sample consisted of 230 persons, including 21 patients who were not in the active phase of the disease. The analysis found a two factor structure: Hallucinatory Experiences and Vivid Mental Events. Using Bayesian inference, we found credible differences between groups in the second factor and overlap in the values of the first factor.